2018
DOI: 10.1001/jamafacial.2018.0570
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Measurement of the Anatomic Features of the Lower Lateral Cartilage and Nasal Tip Shape of the Asian Nose

Abstract: Understanding the nasal tip structure is essential in using a tailored surgical technique for patients with different anatomic characteristics. The width of the alar cartilage determines columellar width and tip bulbosity. 1 The profile contour of the alar cartilage is also a determining factor for rotation, projection, and definition of the nasal tip. 2 Moreover, there is growing recognition of the result of cephalic malposition of the lateral crus in tip aesthetics in the noses of white individuals, thus lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Ethnic considerations are well described in the rhinoplasty and facial plastic surgery literature. 14-21 In the FFS literature, Balaji 22 noted differences in the Indian and Western facial profiles and described “social-cultural ethos” relevant to Indian patients undergoing FFS. Additional dedicated investigations are needed to elucidate race and ethnic considerations in FFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic considerations are well described in the rhinoplasty and facial plastic surgery literature. 14-21 In the FFS literature, Balaji 22 noted differences in the Indian and Western facial profiles and described “social-cultural ethos” relevant to Indian patients undergoing FFS. Additional dedicated investigations are needed to elucidate race and ethnic considerations in FFS.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible hypotheses include discrepancies in health care access, selection bias, and any multitude of health factors influencing surgical candidacy. Ethnic considerations are well described in the rhinoplasty and facial plastic surgery literature 14–21 . In the FFS literature, Balaji 22 noted differences in the Indian and Western facial profiles and described “social‐cultural ethos” relevant to Indian patients undergoing FFS.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a study on Asian ethnicity, 89% of patients undergoing rhinoplasty showed LCCM, yet many of them did not show any tip deformities. 21 In another study on 60 patients in Brazil, 38% had LCCM. 5 The frequency of cephalic malposition in our study was lower than the percentage reported in previous studies (31.3%), which could be due to a larger patient population and Caucasian ethnicity.…”
Section: Discussionmentioning
confidence: 95%
“… 8 Cephalic malposition affects external features, such as nasal tip shape and alar rim, as well as the nasal obstruction results. 9 Various maneuvers are considered specifically to correct this abnormality, such as composite grafts, and repositioning, or even cartilage Z-plasty. 10 Therefore, it is necessary to know the normal range of LCDA to obtain the best aesthetic results.…”
Section: Introductionmentioning
confidence: 99%